1996
DOI: 10.1046/j.1526-4610.1996.3606385.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Primary Headache Syndrome in Adults in the Qassim Region of Saudi Arabia

Abstract: The findings agree with the reported prevalence of 10% to 12% in other communities in the Kingdom of Saudi Arabia, but lower than the rates in Western countries. The lower rates are probably related to sociocultural factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
27
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 15 publications
7
27
2
Order By: Relevance
“…On the other hand, one study conducted in Oman showed a prevalence of headache of about 45% [35], however, that study was among university medical students and not the general population. In nearby Saudi Arabia, the prevalence of primary headaches ranged from 8 to 13% [30, 36, 37], which is much lower than that reported in all other studies from the Middle East area. The higher prevalence of headache in Jordan indicates that it is one of the major health problem.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, one study conducted in Oman showed a prevalence of headache of about 45% [35], however, that study was among university medical students and not the general population. In nearby Saudi Arabia, the prevalence of primary headaches ranged from 8 to 13% [30, 36, 37], which is much lower than that reported in all other studies from the Middle East area. The higher prevalence of headache in Jordan indicates that it is one of the major health problem.…”
Section: Discussionmentioning
confidence: 93%
“…The prevalence of migraine-type headaches in Saudi Arabia is similar to that reported in recent regional and international reports [13-15] but appears to be higher than the rates of previous regional research. Abduljabbar et al [16] found an 8% headache prevalence in Al-Qassim region of Saudi Arabia, with 39% being of the tension type and 32% being migraine. A second study showed that headache prevalence in the town of Al-Thugbah, Saudi Arabia was around 12% and migraine was 5% [17].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence in the literature supporting our results. In almost all epidemiological studies from all over the world, the incidence of headache has been reported to be higher in women than men (1,5,10,12,14,15,16,17,24,27,39,41,43). All the studies (12, 37) have revealed that migraine is two or three times more common in females than males.…”
Section: Arslantas D Et Al: Headache and Its Effects On Health-relatmentioning
confidence: 99%